Pendampingan Peningkatan Kapasitas Manajerial dan Kewirausahaan pada Koperasi Desa: Studi Kasus KDMP Bangunharjo - Gita Danu Pranata; Agus Tri Basuki; Sapardiyono Sapardiyono (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The Merah Putih Village Cooperative (KDMP) in Bangunharjo, Sewon, Bantul faces challenges in management and entrepreneurship, including weak governance, limited business innovation, and suboptimal document management systems. To address these issues, a community service program was conducted by Universitas Muhammadiyah Yogyakarta using Action Research and Participatory Rural Appraisal (PRA) approaches. The program consisted of four stages: preparation, training, mentoring, and evaluation with sustainability planning. Activities included training in cooperative management, basic accounting, local potential-based entrepreneurship, digital marketing, as well as institutional strengthening and archiving systems. The results show a 65.5% increase in participants’ understanding from pre-test to post-test, covering management, accounting, and entrepreneurship aspects. The program also produced a simple business plan, an organized manual archiving system, and initial ideas for business diversification. This initiative is expected to enhance the cooperative’s independence and competitiveness while contributing to the achievement of the Sustainable Development Goals (SDGs).